An Approach to Regional Landuse Classification Using Landsat Imagery - Tiwari, K. P. (Indian Forester, 1976)
Landuse information on macro as well as micro level is a pre-requisite for regional development planning. Land use concept Indian conditions requires a specific approach as not only the different landuse units are highly intermixed but also are highly interactive. The dynamic nature of landuse requires monitoring at less intervals of time Landsat imagery has the capability of imaging large area of land (one frame covers 100 n. miles Ã— 100 n. miles) every 18 days. With proper evaluation techniques, it is possible to recognise macro landuse units and patterns of their distribution including interrelationships. For regional planning the approach adopted in this paper consists of first level classification by broad regional land form units followed by a second level of landuse association units, Third level land use units consist of basic landuse information. statistical significance of the first two levels of classification indicate an efficiency of 126% to 185% for different landuse units indicating useful contribution of landsat imagery for regional planning.